New molecular marker for phylogenetic reconstruction of black yeast-like fungi (Chaetothyriales) with hypothetical EIF2AK2 kinase gene. Issue 12 (December 2020) - Assunção, Cláudia Barbosa; de Aguiar, Edgar Lacerda; Al-Hatmi, Abdullah M.S.; Silva Vieira, Vanessa Cristina; Machado, Amanda Sanchez; Junta, Cristina; de Hoog, Sybren; Caligiorne, Rachel Basques
Abstract: In eukaryotes, phosphorylation of the α-subunit of eIF2 is a mechanism to adjust cellular gene expression profiles in response to specific signals. The eIF2α kinases are a group of serine–threonine kinases that perform important functions in response to infection, proteotoxicity, and nutrient scavenging. The conserved nature of eIF2α kinases among fungi makes them potential evolutionary markers, which may contribute to deeper understanding of taxonomy and evolution. To date, only few studies are available of eIF2α kinases in black yeasts, which are members of Chaetothyriales containing potential agents of a gamut of major human diseases, such as chromoblastomycosis, phaeohyphomycosis and mycetoma. To establish the phylogenetic validity of sequences of eIF2α kinases hypothetical genes, we compared these genes between members of different classes of fungi, including black yeasts and allies, aiming at evaluation of the phylogeny of this group using an alternative molecular marker, compared to standard ribosomal genes. Trees generated with eIF2α kinase sequences of fungi were compared with those generated by ribosomal internal transcribed spacers (ITS rDNA) sequences from the same species. Sequences used were obtained from the protein Non-redundant database of NCBI, were aligned using CLUSTALX v1.8 and alignments were analyzed with RAxML v8.2.9 on the CIPRES Science Gateway portal. The trees generated had similar topologies, demonstrating that eIF2α kinases hypothetical gene sequences present a coherent reflection of evolution among fungi, compared to trees reconstructed by the use of ribosomal sequences. Our preliminary findings with a limited dataset strongly suggest that the evolution of kinases among black yeasts follows a similar path as revealed by ribosomal data, which underlines the validity of current taxonomy of black yeasts and relatives.